2018
DOI: 10.1080/14789949.2018.1513545
|View full text |Cite
|
Sign up to set email alerts
|

Ageing in forensic psychiatric secure settings: the voice of older patients

Abstract: Older patients account for around 20% of the population in secure forensic psychiatric services in the UK. However, little qualitative research has investigated the experience of ageing in secure settings. This study aimed to gather the individual views of a sample of patients over 50 years old in the UK at different levels of security. Fifteen participants were selected and underwent one-on-one qualitative interviews. The interviews were analysed through thematic analysis, which generated seven themes: Self-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 30 publications
1
49
0
1
Order By: Relevance
“…This study is reported according to the principles of the STROBE Statement (Von Elm et al, 2014). It is part of a larger project entitled 'The characteristics, needs and individual experience of older forensic psychiatric patients: A cross-sectional study in three secure units within one regional service', which also comprised two qualitative studies previously published in this journal (Di Lorito, Dening, & Völlm, 2019;Di Lorito, Dening, & Völlm, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…This study is reported according to the principles of the STROBE Statement (Von Elm et al, 2014). It is part of a larger project entitled 'The characteristics, needs and individual experience of older forensic psychiatric patients: A cross-sectional study in three secure units within one regional service', which also comprised two qualitative studies previously published in this journal (Di Lorito, Dening, & Völlm, 2019;Di Lorito, Dening, & Völlm, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Di Lorito et al (2018) in a qualitative study that included service users from all levels of secure settings found that new activities to keep the mind busy, and ageinclusive activities were important for participants. Yorston and Taylor (2009) in their research in a high secure setting, also found that peace and quiet as well as leisure and education opportunities were important to older forensic in-patients in high security, but found in addition that the admission of younger patients to an older ward altered and increased restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory qualitative studies with small numbers of patients in forensic hospitals in Italy (Di Lorito et al, 2017) and Belgium (De Smet et al, 2015) suggested that older forensic in-patients were predominantly positive about the care provided. In a recent UK-based study, Di Lorito et al (2018) argued there were unique challenges to recovery for older service users including lack of awareness of older age issues among staff.…”
Section: Introductionmentioning
confidence: 99%
“…Prisoners suffering from cognitive impairment did not necessarily seek help or consider their quality of life to be affected. Di Lorito, Dening, and Völlm () compared nine studies of older prisoners with similar studies in the community and concluded that the prevalence for dementia in prison studies was in the region of 3.3% and similar to community prevalence but studies indicated that cognitive impairment was more widespread. A link with poor physical health has been highlighted by a study of 310 prisoners in the United States (Ahalt et al, ) who found cognitive impairment to be associated with multiple emergency room visits, hospital admission, and repeat arrests over a 6‐month follow‐up period.…”
Section: Prevalence Of Psychiatric Disorder In Older Prisonersmentioning
confidence: 99%